A cost–utility analysis of etanercept for the treatment of moderate-to-severe psoriasis in Italy - Giorgio L Colombo; Sergio Di Matteo; Ketty Peris; Maria Concetta Fargnoli; et al (Dove Medical Press, 2009)
Giorgio L Colombo1, Sergio Di Matteo2, Ketty Peris3, Maria Concetta Fargnoli3, Maria Esposito4, Annamaria Mazzotta4, Sergio Chimenti41Faculty of Pharmacy, University of Pavia, Pavia, Italy; 2S.A.V.E. Studi Analisi Valutazioni Economiche, Milan, Italy; 3Department of Dermatology, University of L’Aquila, L’Aquila, Italy; 4Department of Dermatology, University of Rome Tor Vergata, Rome, ItalyIntroduction: Biologic therapies have proven efficacious for patients with moderate-to-severe psoriasis. However, their economic value compared with standard of care in Italy has not been explored. This study estimates the cost-effectiveness of intermittent therapy with etanercept in patients with moderate-to-severe plaque-type psoriasis in comparison with nonsystemic therapy in Italy.Methods: This study employs cost–utility analysis using a Markov model adapted from the British “York model”. It compares the cost per quality-adjusted life-year (QALY) of intermittent etanercept (25 mg twice weekly) versus nonsystemic therapy. Data on efficacy and changes in quality of life were derived from three etanercept clinical trials. Direct costs of treating psoriasis patients, including hospitalizations and dermatology clinic visits, were taken from an Italian cost-of-illness study. Extrapolations were made to evaluate the cost-effectiveness of intermittent etanercept versus nonsystemic therapy over a period of ten years.Results: For the group of patients with moderate and severe plaque psoriasis (initial Psoriasis Area and Severity Index [PASI ≥ 10]) the incremental cost-effectiveness ratio (ICER) for etanercept compared with nonsystemic therapy was €33,216/QALY; for the group of patients with severe psoriasis (PASI ≥ 20), the ICER was €25,486/QALY.Conclusions: Within the Italian health care system, intermittent etanercept is a cost-effective therapeutic option compared with nonsystemic therapy for the group of patients with moderate and severe plaque psoriasis. For patients with PASI ≥ 20, cost-effectiveness of etanercept is even greater.Keywords: cost-utility, cost-effectiveness, psoriasis, etanercept, Markov model